XELOX Plus Bevacizumab vs. FOLFIRI Plus Bevacizumab Treatment for First-line Chemotherapy in Metastatic Colon Cancer: a Retrospective Study of the Anatolian Society of Medical Oncology - Duran, Ayse Ocak; Karaca, Halit; Besiroglu, Mehmet; Bayoglu, Ibrahim Vedat; Menekse, Serkan; Yapici, Heves Surmeli; Ozkan, Metin (Asian Pacific Organization Cancer Prevention, 2014)
Background: XELOX plus bevacizumab (XELOX-Bev) and FOLFIRI plus Bevacizumab (FOLFIRI - Bev) treatments are an effective strategies patients with metastatic colorectal cancer (mCRC). The aim of this study was to compare efficacy of first-line XELOX-Bev treatment vs FOLFIRI-Bev treatment for mCRC. Materials and Methods: A total of 409 patients with mCRC who received chemotherapy were included and divided into 2 groups. Group 1 (n=298) received XELOX-Bev and Group 2 (n=111) FOLFIRI-Bev. Comparisons were made in terms of overall (OS) and progression-free (PFS) survival, response rate (RR), and grade 3-4 toxicity. Results: Median follow-up was 11 months in Group 1 and 15 months for Group 2. Complete remission was observed in 29 (9.7%) and 2 (1.8%) patients, partial remission in 139 (46.6%) and 27 (24.5%), stable disease in 88 (29.5%) and 49 (44.1%) and progressive disease in 42 (14.1%) and 33 (30.0%) patients in Group 1 and 2, respectively. Median OS was 25 months (range 2-57 months, 95% CI; 22.2-27.7) for Group 1 and 20 months (range 1-67 months, 95% CI; 16.8-23.1) for Group 2 (p=0.036). Median PFS was 9.6 months (range 2-36 months, 95% CI; 8.8-10.4) for Group 1 and 9 months (range 1-44 months, 95% CI; 7.4-10.5) for Group 2 (p=0.019). Objective RR was 56.4% in Group 1 and 26.1% in Group 2 (p<0.001). Conclusions: First-line XELOX-Bev is more effective with a better response rate, prolongation of median PFS/OS, and a superior safety profile compared with FOLFIRI-Bev.
Keywords: Metastatic colorectal cancer; XELOX plus bevacizumab; FOLFIRI plus bevacizumab; comparison